Management Issues in Medical Industry in Vietnam - Dat Pham Minh; Huy Dinh Tran Ngoc (Zielona Góra: Faculty of Economics and Management Press)
Stock exchange has impacts on activities and capitals of medical companies in Vietnam market. However, medical firms still need researches to address some management issues including good practices of governance, good resources allocation and better risk management policies.
Keywords: medical industry; management; Vietnam; TQM; risk management policie; branża medyczna; zarządzanie; Wietnam; zarządzanie ryzykiem